What does “just” mean in just energy transitions? Different perspectives between EU institutional debates and scientific literature - Giacomo Chiara; Ignazio Terrana; Mauro Sarrica; Sonia Brondi (Frontiers in Political Science)
IntroductionIn light of systemic challenges and radical transformations, such as those at the intersection of energy transitions and justice, there is an increasing need for closer integrations between academic research and policy planning. From this assumption, the current article examines institutional and scientific discourses on just transition to understand which themes and perspectives are common and which areas could benefit from mutual exchanges between the two domains.MethodsThematic analysis of institutional texts about the Just Transition Mechanism and scientific literature on energy and environmental justice (2020-2023) was conducted to uncover shared or disputed discourses. Three overarching aspects and seven sub-themes were highlighted: focus (topics and levels of abstraction), justice (forms and dimensions), and actors (typologies, agency, and relationships).ResultsInstitutional texts emphasize economic-financial stances and restorative or distributive justice, while the scientific literature stresses social stances and recognition or procedural dimensions. A few cross-cutting discourses further organize these results.DiscussionThe prevailing discourse, common in institutional and scientific texts, focuses on criticisms of policy and governance. They advocate for the inclusiveness of Global South actors, reflecting on their agency against (in)just transitions and suggesting strategies for building public engagement and resilience. Overall, institutional and scientific texts reveal internal and reciprocal tensions among themes, with the scientific literature exhibiting greater diversity than institutional debates.